Behavioral ecology of insect parasitoids (Blackwell Pub, 2008)
Written by a team of leading international specialists, Behavioral Ecology of Insect Parasitoids examines the optimal behaviors that parasitoids exhibit in order to maximize long term offspring production. It is an essential reference for research scientists and students studying these fascinating insects or for anyone involved in using parasitoids in biological control programs.